Postnatal epigenetic differences in calves following transient fetal infection with bovine viral diarrhea virus - Jessica N. Kincade; Terry E. Engle; Marcela Henao-Tamayo; Jordan M. Eder; Erin M. McDonald; Darcy M. Deines; Brie M. Wright; Dilyara Murtazina; Jeanette V. Bishop; Thomas R. Hansen; Hana Van Campen (BMC Genomics)
Abstract Background Bovine viral diarrhea virus (BVDV) is the most detrimental pestivirus within the cattle industry. Infection with vertically transmissible BVDV prior to 125 days of gestation results in the generation of a persistently infected (PI) calf. These PI calves are unable to clear the virus in utero, due to an incomplete immune response. However, when infection with BVDV occurs after 150 days of gestation, the fetus clears the transient infection (TI) in utero and is born with antibodies specific to the infecting strain of BVDV. Variations in DNA methylation have been identified in white blood cells (WBC) from TI heifers at birth. It was hypothesized that epigenomic alterations persist into the postnatal period and contribute to previously undocumented pathologies. To study these possible effects, DNA was isolated from the WBCs of 5 TI heifers and 5 control heifers at 4 months of age and subjected to reduced representation bisulfite sequencing (RRBS). Results Differential analysis of the methylome revealed a total of 3,047 differentially methylated CpG sites (DMSs), 1,349 of which were hypermethylated and the other 1,698 were hypomethylated. Genes containing differential methylation were associated with inflammation, reactive oxygen species (ROS) production, and metabolism. Complete blood count (CBC) data identified a higher lymphocyte percentage in TI heifers. When compared in the context of the CD45+ parent population, spectral flow cytometry revealed increased intermediate monocytes, B cells, and CD25+/CD127− T cells, and decreased CD4+/CD8b+ T cells. Comparative analysis revealed differential methylation of CpG sites contained in 205 genes, 5 promoters, and 10 CpG islands at birth that were also present at 4 months of age. Comparison of differential methylation in TI heifers and PI heifers at 4 months of age showed 465 genes, 18 promoters, and 34 CpG islands in common. Conclusion Differential methylation of WBC DNA persists to 4 months of age in TI heifers and is associated with dysregulation of inflammation, metabolism, and growth. Analysis of differential methylation in TI heifers contributes to the understanding of how fetal infection with BVDV induces postnatal detriments related to profit loss.